2006
DOI: 10.1159/000095859
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Standard Photodynamic Treatment Protocol for Symptomatic Circumscribed Choroidal Hemangioma

Abstract: Purpose: To describe the results of photodynamic therapy (PDT) using a standard protocol, developed for treating choroidal neovascularization (CNV), for the treatment of circumscribed choroidal hemangioma (CCH). Methods: A prospective, uncontrolled, consecutive case series of patients with symptomatic CCH that were treated using the standard PDT protocol was evaluated periodically with ophthalmic exams and echography. Results: Nine CCH patients were included in the study. Mean tumor height decreased from 2.7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(60 reference statements)
1
12
0
3
Order By: Relevance
“…However, all studies proved the safety and efficacy of PDT in the case of symptomatic exudative CCH of different activities, sizes and localizations. Complete resolution of serous retinal detachment and/or macular oedema was noted in 89–100% of treated cases . Like in our series, one case had been reported requiring external beam radiotherapy as salvage therapy after five sessions of PDT .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, all studies proved the safety and efficacy of PDT in the case of symptomatic exudative CCH of different activities, sizes and localizations. Complete resolution of serous retinal detachment and/or macular oedema was noted in 89–100% of treated cases . Like in our series, one case had been reported requiring external beam radiotherapy as salvage therapy after five sessions of PDT .…”
Section: Discussionsupporting
confidence: 76%
“…Since the first successful use of PDT to treat CCH by Barbazetto and Schmidt‐Erfurth in 2000, several other studies have reported positive outcomes for CCH with this treatment modality. Studies differed in prospective and retrospective character, patient numbers (3–29 patients) and treatment parameters, including light dose, number of spots, localization of spots, timing of infusion and laser application, number of retreatments, retreatment indications and interval and follow‐up periods . However, all studies proved the safety and efficacy of PDT in the case of symptomatic exudative CCH of different activities, sizes and localizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbazetto et al, 22 Beardsley et al, 27 Blasi et al, 31 Boixadera et al, 35 Elizelde et al, 60 Guagnini et al, 75 Hsu et al, 83 Jurklies et al, 92 KubickaTrzaska et al, 100 Landau et al, 104 Madreperla 112 Michels et al, 123 Nicolo et al, 132 Pilotto et al, 141 Piñeiro-Ces et al, 142 Porinni et al, 143 Robertson et al, 150 Schmidt Erfurth et al, 167 Su et al, 189 Verbraak et al, 207 Vicuna-Kojchen et al, 208 Zhang et al 225…”
Section: Circumscribed Choroidal Hemangiomamentioning
confidence: 99%
“…It has been described in several publications to be safe and effective. Although the treatment protocol differs between publications, the standard protocol may be recommended [16, 17]. However, degenerative changes of the retina may be a result of long-standing exudation limiting the visual outcome when the fovea is involved.…”
Section: Photodynamic Therapy Of Ocular Tumorsmentioning
confidence: 99%